(Letter to the Editor) Response to: protective role of peroxiredoxin-4 in heart failure. (14th January 2020) - López-Andrés, Natalia
Abstract: We thank Ahmed et al. for their letter regarding our study 'Galectin-3 down-regulates antioxidant peroxiredoxin-4 in human cardiac fibroblasts' [1 ]. As emphasized by Ahmed et al., Prx-4 levels decrease [2 ] whereas MFN-2, OPA-1 and PGC-1α levels increase [3 ] in dilated cardiomyopathy (DCM). Moreover, Gal-3 expression is also increased in DCM [4 ]. In our study, we showed in vitro that Gal-3 decreased Prx-4 without modifying MFN-2 or PGC-1α levels in human cardiac fibroblasts. Although cardiac Prx-4 decrease could be a direct consequence of Gal-3 effects on cardiac fibroblasts, we cannot exclude the possibility that other factors increase MFN-2, OPA-1 and PGC-1α levels in both cardiac fibroblasts or cardiomyocytes in the context of DCM. Further studies are needed to clarify the association between Prx-4 decrease and the increase in other mitochondrial proteins in DCM.